Development of Mannitol-Based Microparticles for Dry Powder Inhalers: Enhancing Pulmonary Delivery of NSAIDs - Petra Party; Zsófia Ilona Piszman; Rita Ambrus (Pharmaceuticals, 2025)
Background/Objectives: Chronic lung diseases are among the leading causes of death worldwide. In the treatment of these diseases, non-steroidal anti-inflammatory drugs can be effective. We have previously developed an excipient formulation alongside a modern manufacturing protocol, which we aim to further investigate. We have chosen two new model drugs, meloxicam (MX) and its water-soluble salt, meloxicam-potassium (MXP). The particles in dry powder inhaler (DPI) formulation were expected to have a spherical shape, fast drug release, and good aerodynamic properties. Methods: The excipients were poloxamer-188, mannitol, and leucine. The samples were prepared by spray drying, preceded by solution preparation and wet grinding. Particle size was determined by laser diffraction, shape by scanning electron microscopy (SEM), crystallinity by powder X-ray diffraction (PXRD), interactions by Fourier-transform infrared spectroscopy (FT-IR), in vitro drug dissolution by paddle apparatus, and in vitro aerodynamic properties by Andersen cascade impactor and Spraytec® device. Results: We achieved the proper particle size (<5 μm) and spherical shape according to laser diffraction and SEM. The XRPD showed partial amorphization. FT-IR revealed no interaction between the materials. During the in vitro dissolution tests, more than 90% of MX and MXP were released within the first 5 min. The best products exhibited an aerodynamic diameter of around 4 µm, a fine particle fraction around 50%, and an emitted fraction over 95%. The analysis by Spraytec® supported the suitability for lung targeting. Conclusions: The developed preparation process and excipient system can be applied in the development of different drugs containing DPIs.